A Note on a Theorem of T. J. Rivlin (Analysis in Theory and Applications, 2018)
In this paper, we obtain a result that improves the results of Govil andNwaeze, Qazi and the classical result of Rivlin.
Keywords: Polynomial; maximum modulus; zeros.